Reading the Spiritual Message Behind Javanese Traditional Wedding Procession - Irsyada, Abdulloh Eizzi (Universitas Ciputra, 2023)
This research using qualitative research methods and a descriptive and semotic approach aims to analyze the values and symbolism contained in Javanese traditional wedding processions. With the development of technology and the influence of globalization, the younger generation in Java, Indonesia, tend to leave the traditional Javanese procession in their marriage. This threatens the sustainability and preservation of the cultural heritage. Data was collected through direct observation, interviews and literature study. The series of procedures for traditional Javanese wedding processions and the values contained in each procession are analyzed in depth. The results of the study show that each Javanese traditional wedding procession contains various symbols that reflect the social, religious and cultural values inherent in Javanese society. These symbols have a deep philosophical meaning and are a reflection of the relationship between the bride and groom, family and society. Although it is not an obligation, the use of Javanese traditional ritual processions in marriage for couples with Javanese ethnicity does not have a significant effect on the wedding ceremony or the days afterward, but some couples choose to do it as a form of respect for their ancestors and inherited values, and hope that life their marriage was filled with goodness and blessings passed down by the ancestors.